Judicial activism in South Afica's Constitutional Court : minority protection or judicial illegitimacy? - Sylvia, Tamale (University of Pretoria, 2008)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2007.